Penguatan Peran Dasawisma Sebagai Penggerak Ekonomi melalui Budidaya Tanaman Hortikultura pada Pekarangan di Kelurahan Botang, Kec Makale, Kab Tana Toraja - Dwibin Kannapadang; Oktavianus Pasoloran; Ade Lisa Matasik; Antoni Steven Sirande (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
Limited utilization of household yards and low optimization of horticultural crops remain obstacles to strengthening family economies at the sub-district level. Dasawisma (Family Gardening Group) holds a strategic position as a social unit closely connected to household activities and has the potential to become a driver of the local resource-based economy. This community service program aims to strengthen the role of Dasawisma groups as drivers of the family economy through optimizing horticultural crops in their yards. Implementation methods include outreach, short-term horticultural cultivation training, practical planting assistance, and simple financial record-keeping training. The results of the activity indicate an increase in participants' knowledge about horticultural cultivation, an increased interest in managing their yards effectively, and a strengthening of Dasawisma's collective awareness as household economic agents. This program contributes to changing the community's perspective on yards as economic assets. It was concluded that educational interventions and participatory mentoring were effective in encouraging yard optimization and strengthening Dasawisma's role as drivers of the local economy.